Alat Peringatan Volume Septic Tank dan Netralisasi Kadar Sewer Gas Berbasis Mikrokontroler dan Teknologi Panel Surya - Khakim, Lukmanul; Sulasmoro, Arfan Haqiqi; Afriliana, Ida (Komputika : Jurnal Sistem Komputer, 2023)
The septic tank is a temporary waste disposal site, designed to be closed, there are two holes to drain the reservoir and another hole for evaporation. Septic tanks produce hazardous gases, for example sewer gas, have a pungent odor and are flammable, if the concentration is high, causing poisoning if inhaled, if in a closed room and there is a source of fire, it can trigger an explosion. Therefore, an automation tool is needed as a warning system for the volume of the septic tank and to neutralize the sewer gas level, which has been equipped with solar panels as battery chargers embedded in it. This tool consists of HC-SR04 to measure the remaining volume capacity, MQ2 detects and measures sewer gas levels, a fan to neutralize sewer gas, a buzzer for warning. From the results of this study, the HC-SR04 detects the remaining volume from 28% to 2%, meaning that the volume of the septic tank increases, so the buzzer is active as a notification. Furthermore, MQ2 detects gas concentrations from 2ppm to 64ppm, meaning that the gas concentration increases beyond the safe limit, which is 30ppm, causing the fan to work to neutralize sewer gas levels.